2019
DOI: 10.3389/fnagi.2019.00182
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Retinoid Acitretin Increases IL-6 in the Central Nervous System of Alzheimer Disease Model Mice and Human Patients

Abstract: These days, the important role of retinoids in adult brain functionality and homeostasis is well accepted and has been proven by genomic as well as non-genomic mechanisms. In the healthy brain, numerous biological processes, e.g., cell proliferation, neurogenesis, dendritic spine formation as well as modulation of the immune system, have been attributed to retinoid signaling. This, together with the finding that retinoid metabolism is impaired in Alzheimer’s disease (AD), led to preclinical and early clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…XBP-1 splicing and thereby activation of the transcription factor probability was considered as it has previously been identified as an alpha-secretase gene expression enhancer [ 36 ]. Stimulation of alpha-secretase ADAM10 expression and by this elevation of enzymatic activity could have explained the reduced Aβ deposition and in consequence improved the cognitive function of the mice (e.g., as shown by the pharmacological inducer acitretin, [ 27 ]). However, neither the amount of XBP-1 derived from the unspliced mRNA nor the protein derived from the spliced mRNA was affected in the brains of antibiotics-treated 5xFAD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XBP-1 splicing and thereby activation of the transcription factor probability was considered as it has previously been identified as an alpha-secretase gene expression enhancer [ 36 ]. Stimulation of alpha-secretase ADAM10 expression and by this elevation of enzymatic activity could have explained the reduced Aβ deposition and in consequence improved the cognitive function of the mice (e.g., as shown by the pharmacological inducer acitretin, [ 27 ]). However, neither the amount of XBP-1 derived from the unspliced mRNA nor the protein derived from the spliced mRNA was affected in the brains of antibiotics-treated 5xFAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…The nest building test was performed as described previously [ 27 ]. In brief, animals were habituated to a special nesting material and received 10 g of nesting material for overnight nest building.…”
Section: Methodsmentioning
confidence: 99%
“…This aromatic derivative has also been identified as a potential drug for treating Alzheimer’s disease (AD) in a re-purposing screening attempt 5 . It showed in vitro but also in vivo favorable effects on hallmarks of the disease: for example, it enhanced α-secretase expression and activity in human neuronal cells and in mouse models of the disease 6 , 7 . This enzyme has been demonstrated to be protective against neurotoxic pathways of the disease such as the synthesis of amyloid-β (Aβ) peptides and e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no published data on a possible connection between LCN2 and ADAM10 but several studies support a regulatory role of ADAM10 in TNFα and IL-6 mediated actions. ADAM10 cleaves and thereby mediates the release of TNFα ( Arduise et al, 2008 ) and has also been linked to the regulation of neural IL-6 levels after activation by aromatic retinoid acetritin ( Dos Santos Guilherme et al, 2019 ). It has been further reported that TNFα-induced apoptosis can be regulated via an ADAM10-NF-κB feedback loop in a B cell lymphoma cell line ( Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%